ANALISIS TINGKAT PENJUALAN PENGUSAHA KULINER DENGAN ADANYA PROMOSI DAN DISTRIBUSI MELALUI GRAB FOOD - K Kurniawansyah; Nining Sudiyarti; Surya Doni Atman (Samalewa: Jurnal Riset & Kajian Manajemen, 2023)
The purpose of this study was to determine the effect of promotion and distribution on grab food services on increasing sales of culinary entrepreneurs registered at PT. Grab Sumbawa Besar. This type of this research is associative. The data used in this study is quantitative obtained from primary sources. Primary data in this study is data obtained directly from respondents through distributing questionnaires. The number of samples as respondents in this study was as many as 38 people. All data that has been collected will be processed using the SPSS program to be studied using techniques which include multiple linear regression analysis, partial hypothesis testing (t test), simultaneous hypothesis testing (F test), and determination coefficient test (R2). The results of this study indicate that promotion and distribution have a positive and significant effect on the sales level of culinary entrepreneurs registered at PT. Grab Sumbawa Besar, either partially or simultaneously. The degree of influence of promotion and distribution on the sales level of culinary entrepreneurs registered at PT. Grab Sumbawa Besar is 62.1%, while the remaining 37.9% is influenced by other variables not examined in this study, such as product quality, product selling price, and selling price of competitors' products.